Problematisasi Madrasah dalam Menerapkan Kurikulum Merdeka Pada Pembelajaran Pendidikan Agama Islam - Heny Kusmawati; Lutfi Noor Fajri; Muhammad Fauzan; Muhamad Asyhari (PT Literasi Nusantara Publisher, 2023)
Merdeka Curriculum is a new initiative introduced by the government to give freedom and autonomy to schools in developing their own curriculum. However, in the context of Islamic elementary schools, the implementation of the Independent Curriculum in PAI learning still faces several challenges. This study aims to identify and analyze the problems faced by Madrasah Ibtidaiyah Integrated Al Madani Kaliampo in implementing the Independent Curriculum in learning Islamic Religious Education (PAI). The research method used is descriptive qualitative. Data was collected by distributing questionnaires and interviews. The research subjects were PAI teachers, madrasah heads and student guardians. The results of this study mapped the stages of integrated madrasah ibtidaiyah al madani in facing several problems in implementing the Independent Curriculum in PAI learning.